Implementasi Kebijakan Pengelolaan Sampah Rumah Tangga Di Kabupaten Sumenep - Dewi Ayu Puspitasari; Anggraeny Puspanyngtyas (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2023)
As the time passes and the population increases, the environment will change. One of the causes of the change is the problem of garbage. Waste is a serious problem that needs to be addressed immediately as it affects human lives, directly or indirectly. Sumenep district as one of the regions in Indonesia is growing rapidly, facing an ever-increasing problem of garbage. The study aims to analyze the implementation of household garbage management policy in Sumenep district by identifying supportive and inhibitory factors encountered in the process of implementation in accordance with the policies set out in the Regional Regulations No.83 Year 2018. The method used in this research is a qualitative approach to data collection through interviews and observations. The results of this study use the George Edward III implementation model that covers Communication, Resource, Commitment and Bureaucratic Structure. This research shows that the waste management policy in Sumenep City is not optimal, the resources are not optimal when compared to the amount of garbage that comes in daily, the lack of government commitment, and the socialization of the trash management is not even throughout the Sumenip region.